Amniotic Fluid Analysis at Birth as a Predictor of Canine Neonatal Survival - Reddy, Yeddula Venkata Pridhvidhar; Jayakumar, Chopile; Harshan, Hiron Mooloor; Simon, Shibu; Nair, Sreeranjini Aray ikaravattu Raghavan; Sukumaran, Sajitha Indira (The Indian Journal of Animal Reproduction, 2024)
Establishing dependable indicators for neonatal survival is essential in canine practice. Historically, amniotic fluid has not received attention as a diagnostic tool in dogs. This study analyzed amniotic fluid obtained at whelping from 36 dogs that underwent elective caesarean section (CS) at term to evaluate its potential as a predictor of neonatal survival. Glucose and cortisol concentrations in amniotic fluid were measured at birth in 72 puppies delivered by elective CS. These biochemical parameters were subsequently analyzed to relate puppy survival at birth and neonatal viability, as assessed by APGAR scoring, and to neonatal mortality. The results revealed that stillborn puppies exhibited significantly higher (p<0.001) cortisol and lower (P<0.001) glucose concentrations compared to puppies that survived beyond 48 h post-birth. Although no significant differences in amniotic glucose and cortisol levels were observed across varying APGAR scores, a linear positive trend was noticed between amniotic glucose levels and APGAR scores while the rela tion between amniotic cortisol and APGAR score was linear and negative. From a clinical perspective, the assessment of amniotic cortisol and glucose concentrations immediately following delivery might serve as a valuable tool for identifying neonates that require intensified monitoring during the first 48 h of life.